Rescuing policy in tourism network research - Dianne Dredge (Via@)
Networks provide a powerful lens to understand the complex relations that are transforming social, economic and political life. Through a discussion of the various streams of network research in tourism, this paper argues that policy matters run across and throughout these strands. Rather than arguing for increased interest in tourism policy network research as a separate subfield, the paper argues for deeper theoretical engagement with the policy dimensions in tourism network research. Researchers adopting a network ontology could gain considerable insights and open up new lines of inquiry into what is really going on if they engage with, unpack and critique policy and political science theories, tools, frameworks and concepts.